Impact of MiFID II on Romanian stock market liquidity: Comparative analysis with a developed stock market - Marius Cristian Miloș; Laura Raisa Miloș; Flavia Barna; Claudiu Boțoc (International Journal of Financial Studies, 2021)
In light of previous literature that has investigated the effects of MiFID and MiFID II regulation on stock market liquidity, we investigate whether the introduction of MiFID II in Romania has had any effect on the stock market liquidity. Through our empirical analysis, we were able to estimate a meaningful reduction of liquidity in the Romanian stock market liquidity, in response to MiFID II, in line with the previous empirical literature. We find that the liquidity of the BET index constituents has decreased in the period following MiFID II. We find contradictory results in what concerns the German stock market, which could be explained by the different level of development of the stock markets and of the financial education of investors.
Keywords: 330; Bucharest Stock Exchange; financial regulation; liquidity; MiFID II